4-(x-2)=8-2x

Simple and best practice solution for 4-(x-2)=8-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(x-2)=8-2x equation:


Simplifying
4 + -1(x + -2) = 8 + -2x

Reorder the terms:
4 + -1(-2 + x) = 8 + -2x
4 + (-2 * -1 + x * -1) = 8 + -2x
4 + (2 + -1x) = 8 + -2x

Combine like terms: 4 + 2 = 6
6 + -1x = 8 + -2x

Solving
6 + -1x = 8 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
6 + -1x + 2x = 8 + -2x + 2x

Combine like terms: -1x + 2x = 1x
6 + 1x = 8 + -2x + 2x

Combine like terms: -2x + 2x = 0
6 + 1x = 8 + 0
6 + 1x = 8

Add '-6' to each side of the equation.
6 + -6 + 1x = 8 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 8 + -6
1x = 8 + -6

Combine like terms: 8 + -6 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 3x-2=-2x+18 | | 200+(234+5000)2846= | | x^6+3x^3+1=y^4 | | ln(5x-3)-ln(10x+7)=0 | | z^2-(2i+1)z+i-1=0 | | p^3-6p+6=0 | | 65x=698555 | | (9x-4)(2x-6)+(7x-3)(x+5)-(5x+3)(5x+1)=4 | | 42x^2+20-36=4 | | -m/8-=5/8 | | 5log(x)+2=0 | | 8x-x+19=75 | | 0.91=(0.6-x)+2x | | (0.6-x)+2x=0.91 | | (x+2)(3x+4)-(x-2)(2x-1)-(x+4)(x+3)=26 | | 3(x-5)=5x-7 | | 11-7x=10x+19 | | 2(3p-1)-7=13 | | 2(3x-2)2=6x-4 | | -20-5x=9x+22 | | (2x+1)(x+7)= | | 2y^2+25y-150=0 | | 1=5n | | (6x-15)(3x+20)=(5x-4)(8x+3)-(12+22x^2) | | 15n^2+8n-16=0 | | 4+20m+25m^2=0 | | 7+3m=34 | | 24+10m+m^2=0 | | (3-x)(5+x)-4x=(2-x)(8+x)-x | | y=6x^5-5x^4-30x^3+11x | | 3x^3-x^2+2x-24=0 | | (5x)(-7)+(8)=(6x)(-7)-(7) |

Equations solver categories